2008
DOI: 10.1002/art.23498
|View full text |Cite
|
Sign up to set email alerts
|

Activated memory B cell subsets correlate with disease activity in systemic lupus erythematosus: Delineation by expression of CD27, IgD, and CD95

Abstract: Objective. Analysis of peripheral B cell subsets in patients with systemic lupus erythematosus (SLE) has provided evidence of specific alterations, such as an expansion of CD27؉؉ plasma cells/blasts and transitional B cells. However, memory B cells in lupus have not been thoroughly investigated, and only recently a CD27؊ memory B cell subset was identified in the peripheral blood of lupus patients. Focusing on CD27؊ B cells, this study aimed to identify abnormalities in peripheral B cell subsets in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
217
4
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(249 citation statements)
references
References 32 publications
21
217
4
7
Order By: Relevance
“…The alterations in BAFF, IL-2, and IL-21 in SLE indicate a dysregulation of these factors. Our data in this study demonstrate the B cell differentiation-inducing potential of these factors on memory and DN B cells, which may have an impact in SLE where B cells are known to be in an activated state (106).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The alterations in BAFF, IL-2, and IL-21 in SLE indicate a dysregulation of these factors. Our data in this study demonstrate the B cell differentiation-inducing potential of these factors on memory and DN B cells, which may have an impact in SLE where B cells are known to be in an activated state (106).…”
Section: Discussionmentioning
confidence: 55%
“…There are several hypotheses on the origin of DN B cells including that they are exhausted memory B cells that have downregulated CD27 (109), memory B cell precursors that have not acquired CD27 yet (111), or an entirely new B cell population that has undergone low levels of somatic hypermutation (111,112). DN B cells show an activated phenotype where levels of these cells are associated with higher levels of circulating autoantibodies in SLE (8,106) and have a proinflammatory phenotype in Alzheimer's disease (110). Because of the phenotypic similarity to CD27 + memory B cells defined by cell surface markers such as CD95 shown in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Our data showed the activation of TLR7 also increased the percentage of GC formation and PCs in mice spleens. In addition, it was reported that expanded PCs, which were generated through GCs in both the peripheral and bone marrow in SLE patients, 45,46 are responsible for the production of an array of autoantibodies against soluble and cellular constituents that are most commonly nuclear antigens. 47 Consistent with previous reports, the expression of CCND3 is significantly higher in GC B cells than in non-GC B cells, 7,8 and the expression of miR-15b in IMQ-treated GC B cells is significantly lower than IMQ-treated and wild-type non-GC B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Memory B cells in humans are characterized by the CD27 surface molecule, which is the key marker for these B cells (13), although more recently IgDϪCD27Ϫ B cells that carry features of memory cells have been identified in SLE (14,15). Memory B cells undergo somatic hypermutation in Ig V-region genes, generating Ig rapidly and vigorously in secondary immune responses (16).…”
mentioning
confidence: 99%